Complexation of RNA with mannitol, its spectral characteristics and biological activity - Vivcharyk, M.M.; Ilchenko, O.O.; Levchenko, S.M.; Tkachuk, Z.Yu. (Reports of the National Academy of Sciences of Ukraine, 2016)
The spectral characteristics of the complexation between the RNA and ligands such as mannitol, sorbitol, and lactose, by using the methods of FTIR and FT-Raman spectroscopy and the mathematical model MCR-ALS, are studied. The complexation optimal ratios are determined in the RNA ligand system. In the RNA: mannitol mixture, the ratio is 3 : 1 with complexation about 100 %. In the case of a RNA: lactose mixture, the complexation decreases up to 30 %, and for a RNA: sorbitol mixture, up to 25 %. The results are in a good agreement with the antiviral activity of drugs on the cell culture. The optimal ratio and the better complexation in a RNA: mannitol mixture correspond to the best biological activity of this system. As a result of the replacement of mannitol by lactose in the RNA-ligand system, the biological activity of the preparation changes from antiviral preparation to immunomodulating and anti-inflammatory ones.